Oneness, Seven Worlds, Transmigration, - Interpretations by Commentators and Present-Day Approaches Based on the Source - M.S, Ezhilarasi (International Research Journal of Tamil, 2022)
Thirukkural, which is hailed as a World of Hymn, begins with the blessing of God. So, the book composed on the basis of God's doctrine is Thirukkural. In Thirukkural, when the commentators give explanations for such words as fate, seven worlds, and birth, it is consistent with the principles of religions that do not believe in God. Although many texts have been written for Thirukkural, all but a few have been written largely in imitation of earlier texts. Only a few commentators have looked at the source correctly and have deeply grasped Thiruvalluvar's mind and expressed it in their speeches. An attempt has been made in this research paper to analyze such texts and search for the correct meaning of the words Ezhumai and Ezhrupirappu mentioned by Thiruvalluvar. What is the correct meaning of rebirth? Does that mean seven births? Just as the correct meaning of the words ``unity'' and ``ezhumai'' is asked directly to Thiruvalluvar himself, it has been examined within the Thirukkural book itself by comparing the meaning of one kural with another. A few inconsistencies in the texts have been pointed out by heavily examining only the source. Though it is the text of the best interpreter who has studied and interpreted Thirukkural as if it pierced the atom, the places which appear to be descriptive in relation to knowledge and science have been explored with the aim of finding clarity. This article is examined in the footsteps of the study that was done from the point of view of innovation and thought in the way shown by Thiruvalluvar with the aim of seeing reality.